2007
DOI: 10.1152/ajprenal.00068.2007
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin receptor subtype 2 activation increases cell proliferation in the renal medulla of AQP1 null mice

Abstract: Aquaporin (AQP) 1 null mice have a defect in the renal concentrating gradient because of their inability to generate a hyperosmotic medullary interstitium. To determine the effect of vasopressin on renal medullary gene expression, in the absence of high local osmolarity, we infused 1-deamino-8-d-arginine vasopressin (dDAVP), a V(2) receptor (V(2)R)-specific agonist, in AQP1 null mice for 7 days. cDNA microarray analysis was performed on the renal medullary tissue, and 5,140 genes of the possible 12,000 genes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…RNA isolation, cDNA synthesis, and quantitative PCR were performed as previously described (4). Briefly, total RNA was isolated from mouse inner medullas using an RNeasy Mini Kit followed by cDNA synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, and quantitative PCR were performed as previously described (4). Briefly, total RNA was isolated from mouse inner medullas using an RNeasy Mini Kit followed by cDNA synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney medullas were dissected and RNA was isolated using the Qiagen RNeasy Mini Kit (74104) according to the manufacturer's instructions and per our previous studies (6,24). A DNase (Qiagen, 79254) incubation was performed to remove potential DNA contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 2.5 g of RNA were reverse transcribed and resulting cDNA was diluted to 8 ng/l for real-time PCR which was performed on a RotorGene RG3000 (Qiagen, Valencia, CA). Primer sequences for c-Ret, c-Ret9, c-Ret51, cyclin D1, egr-1, and dynactin are previously published (6,20). Primer sequences for cyclooxygenase (COX)-2 were forward: ttaggctgttggaatttacgc, reverse: cttacagggccttcaaaatgtc.…”
Section: Methodsmentioning
confidence: 99%
“…Mice with a genetic deletion of the gene encoding for the water channel AQP1, which is predominantly expressed in the proximal nephron and essential for generating the countercurrent gradient by significantly increasing water permeability in the thin descending limb of Henle, 64 show an altered proliferation rate of tubular cells in response to vasopressin. 65 Furthermore, a recent phosphoproteomic study in vasopressinresponsive native tubular cells revealed that already short-term vasopressin leads to a slight decrease of cleaved caspases. 53 This study also confirmed decreased activity of MAPKs in response to vasopressin.…”
Section: V2r-dependent Signaling Pathways Are Involved In Controllingmentioning
confidence: 99%